Kesan Modul Pendidikan ‘FLEP’ terhadap Motivasi dan Aspirasi Pembelajaran Pelajar dengan Prestasi Akademik Rendah - Abu Yazid Abu Bakar; Noriah Mohd Ishak; Melor Md Yunus (Jurnal Psikoedukasi dan Konseling)
Abstract: The purpose of this study is to examine effects of the Fun Learning Enrichment Program (FLEP) on motivation and aspiration to learn among low-achievers. The study used quasi experimental design with pre-post control group. A total of 596 students participated in the study for three consecutive years. The students were given a module consisted of 120 fun learning enrichment activities in mathematics and science that promotes self-motivation and aspiration to learn. Results show significant increase in motivation and aspiration to learn among the students after attending the FLEP program. In conclusion, low-achieving students can develop motivation and aspiration to learn when given environment that promotes positive learning experience.